Building contents sliding demands in elastically responding structures. (1st March 2015) - Lin, Sheng-Lin; MacRae, Gregory A.; Dhakal, Rajesh P.; Yeow, Trevor Z.
Highlights: Content sliding demands in elastically responding structures are investigated. Simple analytical expression for content sliding demands is presented. Influence of structural characteristics on content sliding demands is investigated. Empirical formula for content sliding design is proposed and demonstrated. Abstract: This paper quantifies sliding of contents in simple elastic structures subject to ground motion excitation. Contents sliding spectra due to impulse records are developed as a function of normalised friction coefficient, equal to the friction coefficient divided by the structural spectral acceleration in terms of gravity, for structures with different periods. The spectra are not strongly dependent on the structural fundamental period, or the magnitude of the shaking. The total sliding displacement for impulse loading is generally close to that from the first sliding excursion when the normalised friction coefficient is greater than 0.35. However, for lower normalised friction coefficients subsequent sliding excursions also contribute to the total sliding displacement. Simple equations are developed to describe the impulse response. The median total sliding from earthquake motions was represented well by the sliding spectra based on impulse loading. The usefulness of the proposed sliding spectra is illustrated via a design example.